2018
DOI: 10.1159/000481893
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Vitrectomy for Macular Holes after Failure of Vitreolysis

Abstract: Purpose: Ocriplasmin injection may close some small-to-medium macular holes associated with vitreoretinal traction. If the treatment fails, does vitrectomy and gas injection yield the same results as primary surgery? Material and Methods: We report a retrospective case series study of 3 eyes of 3 consecutive patients operated on a few months after initial intravitreal injection of ocriplasmin and enlargement of the macular hole. The minimal follow-up period after surgery was 18 months. Results: Surgery was une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…This is consistent with previous cases showing failure of FTMH closure due to base enlargement following ocriplasmin treatment and subsequent VMA resolution. [37,57] SRF did not have a statistically significant predictive value in our analysis; however, the number of patients showing successful VMA resolution and FTMH closure with SRF were strikingly different between the MIVI-TRUST and OASIS vs ORBIT studies (SRF present: 87% [20/23], 100% [8/8], and 0% [0/30], respectively), perhaps owing in part to differences in SRF measurement protocols at study enrollment and therefore limiting interpretation. In Case 1, presence of SRF did not impact VMA resolution or FTMH closure, although visual acuity improved following SRF resolution.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous cases showing failure of FTMH closure due to base enlargement following ocriplasmin treatment and subsequent VMA resolution. [37,57] SRF did not have a statistically significant predictive value in our analysis; however, the number of patients showing successful VMA resolution and FTMH closure with SRF were strikingly different between the MIVI-TRUST and OASIS vs ORBIT studies (SRF present: 87% [20/23], 100% [8/8], and 0% [0/30], respectively), perhaps owing in part to differences in SRF measurement protocols at study enrollment and therefore limiting interpretation. In Case 1, presence of SRF did not impact VMA resolution or FTMH closure, although visual acuity improved following SRF resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the BCVA values, previous reports [23][24][25] did not find a real risk in delaying the closure of the MH by one month in patients treated with ocriplasmin plus vitrectomy compared to the vitrectomy alone group. Our findings confirm that delaying the vitrectomy in cases that had undergone unsuccessful vitreolytic treatment with ocriplasmin did not affect the clinical success achieved in terms of visual function, and highlighted that these patients might experience better improvement in retinal sensitivity at three months after surgery in comparison to those for which vitrectomy is selected as first-line treatment.…”
Section: Discussionmentioning
confidence: 76%
“…However, on post-operative SD-OCT examination, ellipsoid zone disruption was more frequent in the vitrectomized eyes [25]. Moreover, in a limited case series, Benarous et al [23] showed that failure of treatment with ocriplasmin does not compromise the subsequent anatomical and functional success of postponed vitrectomy for macular holes.…”
Section: Discussionmentioning
confidence: 98%
“…VMT was estimated to be present in 34% of FTMHs, and in only 13% of small FTMHs. 51 , 52 There is no relationship between the FTMH size and the presence of VMT. 75 The most relevant consideration in this type of FTMHs when they are small (<250µm) is the possibility of performing a nonsurgical technique, namely a IVI of ocriplasmin.…”
Section: Surgical Outcomes Of Inverted Ilm Flap Techniquementioning
confidence: 98%
“… 50 Vitrectomy, ILM peeling, and gas tamponade have shown efficacy in small FMTHs that failed to close after IVI of ocriplasmin. 51 To our knowledge, no studies have reported the anatomical and functional results of the inverted ILM flap technique in FTMHs ≤250µm. Instead, most studies used the cut-off of 400µm to differentiate between small to medium and large FTMHs.…”
Section: Surgical Outcomes Of Inverted Ilm Flap Techniquementioning
confidence: 99%